Analysis of Positioning at Kasih Ibu Hospital Surakarta - Muhamad Marwan Dhani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Kasih Ibu Hospital is one of the private B type hospitals in Surakarta residency which is facing a tight competition in maintaining its quality in proportion to its income. Kasih Ibu Hospital competes with other type B hospitals, namely X Surakarta Hospital and Y Hospital Surakarta. This research used a descriptive method. The population was the service users of Kasih Ibu Hospital, X Hospital Surakarta and Y Hospital Surakarta. A sample of 50 people was taken by accidental sampling. Data collection was by questionnaire. Data analysis was performed by Multidimensional Scaling (MDS) and biplot perception maps. X Hospital Surakarta is the closest competitor of Kasih Ibu Hospital Surakarta, with a Euclidean distance of 2.8127. X Surakarta Hospital, more prominent intangibles, and empathy dimensions. Kasih Ibu Hospital Surakarta is more prominent in the dimensions of responsiveness, and at a lower level is the reliability and assurance dimension. Y Hospital Surakarta does not specifically stand out on the dimension of service quality based on patient perception. The dimensions which although not too prominent but the closest are empathy. X Surakarta Hospital is the closest competitor of Kasih Ibu Hospital Surakarta. X Hospital Surakarta, more prominent intangibles and empathy dimensions. Kasih Ibu Hospital Surakarta is more prominent in the dimensions of responsiveness, and at a lower level is the reliability and assurance dimension.